Efficacy and safety of open‐label caplacizumab in patients with exacerbations of acquired thrombotic thrombocytopenic purpura in the HERCULES study. (9th December 2019) - Knoebl, Paul; Cataland, Spero; Peyvandi, Flora; Coppo, Paul; Scully, Marie; Kremer Hovinga, Johanna A.; Metjian, Ara; de la Rubia, Javier; Pavenski, Katerina; Minkue Mi Edou, Jessica; De Winter, Hilde; Callewaert, Filip
Abstract: Background: Acquired thrombotic thrombocytopenic purpura (aTTP) is a rare, life‐threatening autoimmune thrombotic microangiopathy. Caplacizumab, an anti‐von Willebrand Factor Nanobody ®, is effective for treating aTTP episodes and is well tolerated. Objectives and methods: In the phase 3 HERCULES trial (NCT02553317), patients with aTTP received double‐blind caplacizumab or placebo during daily therapeutic plasma exchange (TPE) and for ≥30 days thereafter. Patients who experienced an exacerbation while on blinded study drug treatment switched to receive open‐label caplacizumab plus re‐initiation of daily TPE. Exacerbations were defined as recurrence of disease occurring within 30 days after cessation of daily TPE. Results: Thirty‐one patients (placebo, n = 28; caplacizumab, n = 3) had an exacerbation during double‐blind treatment. Twenty‐eight patients switched to open‐label caplacizumab (placebo, n = 26; caplacizumab, n = 2); the three others discontinued upon exacerbation. Median time to platelet count response (≥150 × 10 9 /L) was 3.49 days upon receiving caplacizumab. There were no deaths. During open‐label treatment, further exacerbation or a major thromboembolic event (vena cava thrombosis) was experienced by one patient (3.6%) each. Consistent with the double‐blind phase, the most frequent treatment‐emergent adverse events were catheter site hemorrhage (28.6%), headache (21.4%), and epistaxis (17.9%). Conclusions: These results suggest that caplacizumab was efficacious and well tolerated in patients with aTTP who experienced a disease exacerbation during double‐blind treatment in HERCULES.